Joining of AZ31 and AZ91 Mg alloys by friction stir welding - B. Ratna Sunil; G. Pradeep Kumar Reddy; A.S.N. Mounika; P. Navya Sree; P. Rama Pinneswari; I. Ambica; R. Ajay Babu; P. Amarnadh (Journal of Magnesium and Alloys, 2015)
Two dissimilar magnesium (Mg) alloy sheets, one with low aluminium (AZ31) and another with high aluminium (AZ91) content, were successfully joined by friction stir welding (FSW). The effect of process parameters on the formation of hot cracks was investigated. A sound metallurgical joint was obtained at optimized process parameters (1400 rpm with 25 mm/min feed) which contained fine grains and distributed β (Mg17Al12) phase within the nugget zone. An increasing trend in the hardness measurements has also confirmed more amount of dissolution of aluminium within the nugget zone. A sharp interface between nugget zone and thermo mechanical affected zone (TMAZ) was clearly noticed at the AZ31 Mg alloy side (advancing) but not on the AZ91 Mg alloy side (retreating). From the results it can be concluded that FSW can be effectively used to join dissimilar metals, particularly difficult to process metals such as Mg alloys, and hot cracking can be completely eliminated by choosing appropriate process parameters to achieve sound joint.